Analysis of Learning Difficulties of Grade XII Students in Genetics at SMA 4 Tanimbar Selatan - Edy Rupilele (Universitas Victory Sorong, 2025)
Genetics is one of the biology materials considered difficult by students because it contains abstract concepts, scientific terms, and complex processes. This study aims to: 1) Describe students' learning difficulties in genetics material for grade XII at SMA Negeri 4 Tanimbar Selatan. 2) Describe the factors causing students' learning difficulties in genetics material for grade XII at SMA Negeri 4 Tanimbar Selatan. 3) Describe the efforts made by biology teachers in overcoming students' learning difficulties in genetics material for grade XII at SMA Negeri 4 Tanimbar Selatan. The approach used in this study is qualitative with a case study research type. Data collection techniques used are observation, interviews and documentation. Data analysis is data condensation, data presentation and drawing conclusions. Data validity uses triangulation techniques and triangulation sources. The results of this study indicate that: 1) Students' learning difficulties in genetics material for grade XII at SMA Negeri 4 Tanimbar Selatan are that most of the students experience learning difficulties characterized by low student learning outcomes or below the KKM. 2) The factors causing learning difficulties are internal factors, namely students' lack of learning motivation and external factors, namely the teacher's teaching methods and learning media that are less interesting. 3) Efforts made by biology teachers in overcoming students' learning difficulties in genetics material for grade XII at SMA Negeri 4 Tanimbar Selatan include providing motivation to students, holding discussions with peers, conducting assessments that can be taken from various aspects, namely knowledge, attitudes and skills.